Introduction to Information and Communication Technologies for Development (ICTD) Minitrack: Contributing to Human Development and Social Justice (2015)
This minitrack explores opportunities to use Information and communication technologies to promote human development and social justice. In the early days this field began with radio and television as tools to help improve the lives of marginalized communities, but this has now become a global movement of people using computers, the internet, and mobile devices to help human development. Information technologies have become more accessible, more used, and more relevant than ever in the lives of people around the world. A growing body of scholars and researchers work to understand, design, evaluate and critique ICTD interventions, which can bring numerous benefits as well as unanticipated negative consequences to those affected.